Short-term lower-body plyometric training improves whole-body BMC, bone metabolic markers, and physical fitness in early pubertal male basketball players - Zribi, A.; Zouch, M.; Chaari, H.; Bouajina, E.; Nasr, H. B.; Zaouali, M.; Tabka, Z. (Pediatric Exercise Science, 2014)
The effects of a 9-week lower-body plyometric training program on bone mass, bone markers and physical fitness was examined in 51 early pubertal male basketball players divided randomly into a plyometric group (PG: 25 participants) and a control group (CG: 26 participants). Areal bone mineral density (aBMD), bone mineral content (BMC), and bone area (BA) in the whole body, L2-L4 vertebrae, and in total hip, serum levels of osteocalcin (Oc) and C-terminal telopeptide fragment of Type I collagen (CTx), jump, sprint and power abilities were assessed at baseline and 9 weeks. Group comparisons were done by independent student`s t-test between means and analyses of (ANOVA) and covariance (ANCOVA), adjusting for baseline values. PG experienced a significant increase in Oc (p < .01) and all physical fitness except for the 5-jump test. However, there was no improvement in aBMD, BMC and BA in any measured site, except in whole body BMC of the PG. A positive correlation was observed between percentage increase (delta%) of physical fitness and those of (Oc) for the PG. In summary, biweekly sessions of lower body plyometric training program were successful for improving whole body BMC, bone formation marker (Oc) and physical fitness in early pubertal male basketball players.